Lower-limb motor-performance asymmetries in English community-level female field hockey players: Implications for knee and ankle injury prevention. (May 2020) - Clark, Nicholas C.; Clacher, Lucy H.
Abstract: Objectives: Side-to-side asymmetry of lower-limb motor-performance is associated with increased agility-sport noncontact injury-risk. Left leg preferential use (unilaterality) in hockey may influence lower-limb motor-performance asymmetry. Symmetry-analyses have not been reported for female hockey players. This study performed symmetry-analyses using the eyes-closed-balance test (ECB), anterior reach test (ART), triple-hop-for-distance (THD), and six-metre hop-for-time (6MHT). Design: Cross-sectional. Setting: Community-level club. Participants: Thirty players (age 25.6 ± 4.5yr; height 165.6 ± 5.9 cm; mass 64.8 ± 5.5 kg). Main outcome measures: Right-left group-level ( t -test with Bonferroni adjustment) and individual-level (absolute-asymmetry (%)) comparisons. A limb symmetry index (LSI) was computed for each player and a clinically-significant absolute-asymmetry defined >10% as per previous literature. Clinically-significant absolute-asymmetry prevalence (%) was calculated across tests. For unilaterality, prevalence of superior left-side performance was calculated. Results: There were no right-left significant differences across tests. Findings for ECB, ART, THD, and 6MHT were: absolute-asymmetry, 28.7 ± 26.9%, 3.5 ± 2.8%, 3.5 ± 3.4%, 6.1 ± 4.7%; prevalence of clinically-significant absolute-asymmetries, 70.0%, 3.3%, 6.7%, 26.7%; prevalence of superior left-side performance, 46.7%, 53.0%, 50.0%, 47.0%. Conclusions: Statistical tests fail to expose clinically-significant absolute-asymmetries. Many players demonstrated clinically-significant absolute-asymmetries for ECB and 6MHT tests. Clinical interpretation of LSIs and absolute-asymmetries need not consider unilaterality. Clinically-significant absolute-asymmetries previously linked to injury-risk are common in a community-level, adult female hockey players. Highlights: Clinically-significant asymmetries are not exposed by group-level statistics. The majority had clinically-significant asymmetry for the eyes-closed-balance test. Many players had clinically-significant asymmetry for the six-metre hop-for-time. The unilaterality of hockey does not affect interpretation of absolute-asymmetries. Clinically-significant asymmetry is widespread in a community-level adult hockey.